Implementation of the spatial plan information package for improving ease of doing business in Indonesian cities. (June 2021) - Indrajit, Agung; van Loenen, Bastiaan; Suprajaka,; Jaya, Virgo Eresta; Ploeger, Hendrik; Lemmen, Christiaan; van Oosterom, Peter
Abstract: Land and space are major driving factors in doing business in urban areas. Cities around the world are performing land management techniques to achieve sustainable urban development. The World Bank acknowledges the importance of land management practices and promotes it as the Ease Of Doing Business (EODB) indicators for a supportive environment for economic activities. In improving a city's competitiveness, local governments need to establish a reliable Land Administration System to organize unrenewable urban land and spaces and simultaneously reduce information asymmetry between actors. A modernized LAS is needed to accommodate the four functions of land management: land tenure, land value, land-use planning, and land development. The ISO 19152:2012 on Land Administration Domain Model (LADM) standard offers a foundation to establish information interoperability in land management that is crucial in modeling the relationship between people and land (and space), the geometrical components, as well as documented Rights, Responsibilities, and Restrictions (RRRs) in land. To promote the exchange of information between the domains of land administration domain and spatial planning, an extension of LADM, the Spatial Plan Information Package (SP Package), was proposed to support cities organizing information in land management. This article presents the proposed spatial plan information extension to the LADM country profile for Indonesia. This work also develops a proof-of-concept of the package in the two biggest Indonesian cities (Jakarta and Bandung) with adaptation to the current national data management policies. Our research shows positive results on making the LADM country profile reflect on the real condition and improving LAS's adaptability to be integrated with the Spatial Information Infrastructure. Highlights: How to improve the LADM country profile using Spatial Planning Information Package. How to strengthening data governance for supporting a city to achieve sustainable development and ease of doing business. Lessons learned in the development of multidimensional visualization or RRRs from land land-use planning.